(untitled) (Global Journal of Human-Social Science, 2015)
Poverty and attempts to alleviate it is an issue that has continued to generate interest of national governments and international agencies and mostly in developing countries including Kenya. The Christian Church, in spite of its central mandate being spiritual evangelism has continued to participate in the fight against poverty to accomplish Jesus Christ’s mission to whole-heartedly serve and minister to all; both rich and poor of the world. This study sought to evaluate the role that the Anglican Church of Kenya (ACK) plays in helping to alleviate poverty amongst its faithful. Specifically, the study set out to investigate the type and nature of development programmes carried out by the Church in Maseno and Winam divisions of Kisumu District; to assess the capacity of the ACK to manage the programmes; and, to establish the influence of the development programmes on the people. The Church, due to its proximity to the poor, remains one of the major stakeholders of poverty alleviation in rural areas. Hence, the study made the assumption that the majority of people living in Maseno and Winam divisions are not only poor but also profess the Christian faith as adherents of this church.